Constructivist and Humanistic Learning Theories in Islamic Religious Education (IRE): Student-Centered Learning Approaches - Dinda Jumiati; Amellia Putri Syahrani; Salmaini Yeli (unprimdn.ac.id, 2025)
This study examines the application of constructivist and humanistic learning theories in Islamic Religious Education (IRE) through a student-centered learning approach. Constructivist theory posits that knowledge is actively constructed by learners through experience, reflection, and environmental interaction, while humanistic theory emphasizes the holistic development of human potential encompassing cognitive, affective, and psychomotor domains, aligned with the Islamic concept of humans as vicegerents on earth. The integration of these theories in IRE pedagogy creates an interactive and meaningful learning environment that honors individual uniqueness. Within this framework, teachers function as facilitators, mediators, and motivators who guide students toward self-actualization through contextual and collaborative learning activities. The constructivist-humanistic approach demonstrates significant advantages in enhancing learner autonomy, critical thinking skills, and the formation of religious character. However, its implementation faces substantial challenges, including limitations in teacher competency, instructional time constraints, and availability of contextual learning resources. Therefore, professional development initiatives for educators and the development of adaptive IRE curricula are essential to ensure effective implementation of both theoretical frameworks in learning practice.